Antimicrobial and sorption properties of polymer films based on modified starch with xeroform for veterinary purposes - Kuchynska, Daria; Ishchenko, Olena; Kachan, Roman; Sumska, Olha; Roik, Olena (Technologies and Engineering, 2025)
The development of effective and safe wound healing materials is becoming exceedingly important in veterinary medicine, particularly concerning the treatment of infected wounds and the prevention of secondary infections. A promising strategy involves the fabrication of polymeric films possessing combined functionalities. The aim of this study was to evaluate the antimicrobial and sorption properties of polymer films based on a blend of modified starch and polyvinyl alcohol, containing 10 wt.% xeroform, for their potential application as veterinary dressing materials. The antimicrobial activity of the films was determined using the agar diffusion method against Escherichia coli, Staphylococcus aureus, Candida albicans, and Aspergillus niger; sorption characteristics were evaluated based on water uptake kinetics and methylene blue dye adsorption, measured by photoelectric colorimetry. The investigated films demonstrated pronounced antibacterial and fungicidal activity against all tested strains of modern wound pathogens, confirming the efficacy of xeroform within the polymer matrix, exhibiting complete inhibition against Escherichia coli, Staphylococcus aureus, Candida albicans, and Aspergillus niger. Additionally, the compositions exhibited high liquid absorption capacity, essential for exudate removal from the wound surface, with water uptake ranging from approximately 180% to over 230% at equilibrium and methylene blue adsorption exceeding 50% within 60 minutes. The kinetics of water uptake and methylene blue dye adsorption were significantly dependent on the starch modification conditions and the modified starch / polyvinyl alcohol blend ratio in the composition. The obtained results indicate the potential of the developed modified starch / polyvinyl alcohol / xeroform films as active wound healing coverings with integrated bioactive components (antiseptics) for veterinary use, possessing antiseptic and high sorption properties that contribute to therapeutic efficacy. The possibility of varying the starch modification conditions and composition allows for targeted regulation of the material’s functional characteristics to adapt them to specific clinical needs and animal species